El populismo según Ernesto Laclau: problemas en la definición de un concepto (2018)
Recognizing the actuality and interest that has and provokes the phenomenon of populism, it is proposed to seek the definition that provides greater clarity and utility. In this way we begin by exposing the presuppositions of populism as understood by Ernesto Laclau. Subsequently, the gaps in your proposal are indicated. Thus, we come to the perspective of Jacques Rancière, to understand politics as a practice of radical inclusion, which is used to respond to criticisms of lack of specificity that are made to the Argentine thinker and pointed out the possible problems that can have the approaches of different commentators. Finally, it is argued that populism is a democratic phenomenon and also a process of radical inclusion, an assertion based on the understanding of democracy as a historical transformation. This definition pretends to be a surpassing of the problems of abstraction and excessive specificity that have been distinctive features of the investigations carried out around the concept of populism that provides more clarity when analyzing concrete cases.